Defence and development: a case study of the Philippines - Avila-Goldman, A P (Cranfield University, 2016)
In the security spectrum, there is a blurring line between defence and development. In both traditional and non-traditional security situations, such as counterinsurgency and natural disasters, the armed forces has been called to respond in ways other than their mandate of physical protection in order to attend to human development needs. How and when this transition of roles happens has been studied and debated. As the main security institution of a country, militaries around the world have performed duties outside of their defence functions. Their tasks have expanded from maintaining peace and order to including nation-building, economic development, the provision of disaster relief, and engaging in efforts to conserve natural resources. Looking at these extra functions, the Philippines armed forces are no different in performing non-traditional roles. The Armed Forces of the Philippines (AFP) is one of the key institutions, which has been at the forefront of the campaign in tackling these domestic challenges. To a certain extent, the mixture of economic activities with combat operations has characterised the military’s different campaigns such as counter-terrorism and counter-insurgency. Involvement in economic functions has been justified on the grounds that it is critical to ‘winning the hearts and minds’ of those living on the front lines, supporting the military’s role in nation-building. The aim of this study is to employ pre-determined metrics to evaluate the contribution of the Philippine defence sector to national development, and, in turn, comprehensive security. Whilst the conventional view is that defence is a burden on development, the question this study poses is whether, by contrast, in the Philippine context, there is a positive relationship between defence and development; that is, that defence expenditure contributes to development outputs such as employment, skill-generation and even infrastructural investment. The study framework is anchored to the following policies: AFP Modernisation Act of 1995, and its subsequent revision, AFP Modernisation Act of 2010, the Internal Peace and Security Plan (IPSP), and the National Security Plan 2011-2016. The framework highlights the important security goals of defence industrialisation, internal security, and non-traditional security. These data were further substantiated and consolidated via archival sources, such as government and company reports, as well as secondary data (e.g. books, journals, etc.). The mission thrusts of the AFP demonstrate the organisation’s multiple objectives to carry out a mandate to protect the state and the people. The Philippines has a very modest defence industry with few companies manufacturing small arms and ammunitions. Its goal is to be self-reliant, however, issues within the Procurement Law prevents this. Meanwhile, the conduct of counter-insurgency efforts through the IPSP allows the AFP unified commands and field units to support government units and agencies in their peace and development programmes. Furthermore, the geographic deployment of military personnel and equipment across the archipelago allows the armed forces to respond in times of disasters. Overall, the armed forces has contributes positively to the national development of the Philippines. To this end, and based on the research finding, a number of important policy recommendations are advanced to raise the effectiveness of the Philippines’ security policies.
Keywords: Civil-military relations